Paleomagnetism of Eocene and Miocene sediments from the Qaidam basin: Implication for no integral rotation since the Eocene and a rigid Qaidam block - Xiangjiang Yu; Suotang Fu; Shuwei Guan; Baochun Huang; Feng Cheng; Xiang Cheng; Tuo Zhang; Zhaojie Guo (Geochemistry, Geophysics, Geosystems)
Abstract The Qaidam basin is the largest topographic depression inside the Tibetan Plateau and it is a key factor to understanding the Cenozoic evolution of the northern Tibetan Plateau. Paleomagnetic data was obtained from the middle to late Eocene Xiaganchaigou Formation and the early to middle Miocene Xiayoushashan Formation from seven localities. The paleomagnetic results indicate that the Qaidam basin has not undergone obvious basin‐scale vertical axis rotation with respect to the Eurasia Plate since the Eocene. Local clockwise rotation took place only at a few special locations along the northern margin of the Qaidam basin. The uniform paleomagnetic results at different localities support that the Qaidam basin is a relatively rigid block. Regional paleomagnetic and geodetic observations also suggest that crust south of the Kunlun fault moves eastward faster than crust north of the Kunlun fault.